Recent advances in understanding cross-talk between Bile Acids and Gut Microbiota - Cheng-cheng Feng; Ai-hua Zhang; Jian-hua Miao; Hui Sun; Ying Han; Guang-li Yan; Fang-fang Wu; Xi-jun Wang (Open Journal of Proteomics and Genomics - Peertechz Publications, 2018)
Bile acid (BA) plays an important role in the absorption and translocation of fat and fat-soluble vitamins. In addition, it can also act as a signaling molecule to influence the energy metabolism of organisms, glucose metabolism, and the development of liver and intestinal diseases by activating receptor. Gut microbiota participates in the metabolism and transport of BA, which changes the BA associated with the occurrence and development of a variety of diseases. This is achieved through a variety of regulatory processes and is intrinsically linked to host physiology. In recent years, many scholars have used 16S rRNA gene sequencing in conjunction with serum, urine, and fecal metabolomics methods to study the mechanisms underlying the occurrence and development of disease associated with BA and gut microbiota, or to evaluate the protective action of drugs on the metabolic phenotype in rats with gut microbiota disorder. On the one hand, the gut microbiota regulates BA by activating receptors such as FXR, TGR5, and FGF15, and can regulate BA synthesis through enzyme reaction. In addition, gut microbiota can effectively hydrolyze bound parasites or heterogenous organisms that have been cleared by BA. On the other hand, BA can alter the composition of the gut microbiota by inhibiting the growth of bacteria in the intestine. These studies provide new ideas for further elucidating the relationship between gut microbiota and BA and treatment for related disease.